TEACHING GOOD CHARACTER IN A NARRATIVE TEXT THROUGH STORYTELLING - Maidhina Keisha Rahasya (Journal of English and Education, 2017)
This research paper entitled “Teaching Good Character in a Narrative Text through Storytelling” was aimed at discovering the teaching of good character of respect in a narrative text through storytelling and the students’ responses to the teaching of good character of respect in a narrative text through storytelling. The good character was respect and the story used in this research entitled “Gilbert the Goat Learns Respect” was produced by MyYoungChild.org in 2012. The eighth grade students became the participant of this research and to collect and identify the data, qualitative method was applied equipped with descriptive analysis with observation, questionnaire and document analysis as the instrument of the research. The result of the study showed that the teaching of good character of respect in a narrative text is taught through storytelling relatively faithful to the framework of Ellis and Brewster (1991) that have three steps namely pre-storytelling step, during storytelling step and after storytelling step. Some activities in each step also help the students in learning good character of respect.  From this teaching, the students were able to make a reflection from the story and showed their behavior of being respectful through the reflection. For the responses, almost all of the students showed positive responses to the help of storytelling in teaching good character of respect in a narrative text through storytelling. This model of teaching is handy for teacher to teach good character of respect in a narrative through storytelling in more well-prepared method.